Strong convergence theorems for equilibrium problems with nonlinear operators in Hilbert spaces - S. Dhompongsa (2018)
In this paper, we introduce an iterative sequence for finding a common element of the set of fixed points of a nonspreading mapping, the set of solutions of an equilibrium problem and the set of solutions of the variational inequality problem for a monotone and Lipschitz-continuous mapping in a Hilbert space. We show that the sequence converges strongly to a common element of the above three sets. © 2012 Yokohama Publishers.